Repatriate career management practices in Finnish multinational companies. - Nilsson, Max (My University, 2014)
The purpose of this study is to examine career management practices of seven Finnish multinational companies. The aim is to examine which career management practices are in use upon repatriation and how do they impact the repatriates in terms of career capital. The study is conducted from the organization’s perspective. Consequently the main research questions are: Which HR processes and practices are utilized to manage the career management of repatriates/expatriates and How do the HR practices relate to the career capital areas of knowing-how, knowing-whom and knowing-why. The literature review examines the importance of career management in repatriation adjustment was explained. It introduces repatriate career management practices that are claimed to benefit the career development of the repatriate. Then the concept of capital is described and a linkage to the practices is made. An empirical study is made about how the Finnish multinational companies manage their career support of repatriates and how the companies deal with complexities occurring in the process. The interviews examine the phenomenon of career management of repatriates within multinational corporations from the view of the organization. This study adopts a positivist approach, which implies a prior assumption that there are discoverable relationships between HR practices, career management of repatriates and career capital. A relationship between the practices and the accumulation was found. It can be said that Finnish companies engage in repatriate career management to some extent but also stress the individual’s responsibility. The companies did not knowingly try to influence the 3 different areas of knowing, meaning they had not implemented the concept of career capital in their HR practices. The companies did stress the importance of gaining new skills, international assignment’s potential in creating networks and networking and maintaining a healthy relationship with the individual that is based on trust and mutual understanding.
Keywords: career management; career capital; expatriation; repatriation; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|